Improving Organizational Citizenship Behavior through Organizational Competence and Commitment as a Mediation Variable - Ampauleng, Ampauleng; Abdullah, Salma; Maulana, Achmad Amzal (Universitas Pancasakti, 2025)
Research on performance management-based views has been the main framework of many human resource management research, the literature shows that much of the research is conducted with a major emphasis on performance management-based views in exploring the improvement of organizational citizenship behavior through employee competence and organizational commitment as a mediating variable. This study aims to analyze the influence of employee competencies on Organizational Citizenship Behavior (OCB) behavior with organizational commitment as a mediating variable. OCB is the voluntary behavior of employees that goes beyond their formal duties and contributes to the effectiveness of the organization. Employee competencies, which include knowledge, skills, and attitudes, are considered an important factor in driving OCB behavior. However, the relationship between competence and OCB can be influenced by the level of organizational commitment that employees have. This study uses a quantitative approach with a survey method on a number of employees at the Makassar City Regional Drinking Water Company. The sample determination technique uses a simple random sampling technique, so that a sample of 86 people was obtained. The data analysis technique used multiple linear regression analysis using the help of Smart PLS 4 software. The results of the analysis show that competence has a significant effect on organizational citizenship behavior, organizational commitment has a significant effect on organizational citizenship behavior, competence has a significant effect on organizational commitment and, competence has a significant effect on organizational citizenship behavior through organizational commitment. This research provides practical implications for organizational management in designing competency development programs that are integrated with efforts to increase organizational commitment, in order to encourage Organizational Citizenship Behavior that contributes to overall organizational performance.